2017
DOI: 10.1016/j.atherosclerosis.2017.10.027
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome pathways in atherosclerosis

Abstract: Atherosclerosis is the major cause of death and disability. Atherosclerotic plaques are characterized by a chronic sterile inflammation in the large blood vessels, where lipid-derived and damage-associated molecular patterns play important roles in inciting immune responses. Following the initial demonstration that NLR family Pyrin domain containing 3 (NLRP3) was important for atherogenesis, a substantial number of studies have emerged addressing the basic mechanisms of inflammasome activation and their releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(120 citation statements)
references
References 149 publications
(177 reference statements)
1
118
0
1
Order By: Relevance
“…24,25 Previous studies suggested that several signaling pathways, including signals produced by inflammasomes and endoplasmic reticulum stress are involved in the occurrence and development of atherosclerosis. 14,26,27 However, the regulatory mechanism of atherosclerosis is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Previous studies suggested that several signaling pathways, including signals produced by inflammasomes and endoplasmic reticulum stress are involved in the occurrence and development of atherosclerosis. 14,26,27 However, the regulatory mechanism of atherosclerosis is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…12 NLRP3 inflammatory corpuscles can be activated by a variety of pathogenic microorganisms and risk signals, and participate in the occurrence of numerous human diseases. 13,14 There is also evidence that apoptosis signal-regulating kinase 1 (ASK1) is required for NLRP3 inflammasome activation. 15 However, it is not clear whether ox-LDL-mediated cholesterol efflux is associated with ERS, ASK1, and NLRP3 inflammatory corpuscles.…”
Section: Introductionmentioning
confidence: 99%
“…IL-1␤ plays a pivotal role in signaling of other inflammatory cytokines. Emerging evidence suggests a key role for the inflammasome in atherosclerotic disease progression (73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83) and in HIV-1 disease (47,(84)(85)(86)(87)(88)(89). Inflammasome activation requires two signals, one for priming (i.e., TLR signaling which results in transcriptional regulation) and then one for activation of inflammasome complex assembly.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the NF‐κB pathway in the atherosclerotic lesions’ macrophages promoted monocytes infiltration and plaque development 83 . Moreover, oxidized mtDNA, which escaped degradation by autophagy, was reported to activate the NLRP3 inflammasome thus regulating the release of cytokines, such as IL‐1β and IL‐18 84,85 . In addition, mitochondrial dysfunction was also shown to affect the cholesterol efflux in macrophages 86 .…”
Section: Mitochondrial Dna Damage In Macrophagesmentioning
confidence: 99%